RESISTANCE AND POTENTIAL YIELD TEST OF ACCESSION TOMATO DETERMINATE HYBRID (F1) TO TOMATO YELLOW LEAF CURL VIRUS (TYLCV) - Chitia Novita Sari; Lagiman Lagiman; Endah Wahyurini (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
This study aimed to determine the resistance and yield of accessionized determinate hybrid tomatoes (F1) against Tomato Yellow Leaf Curl Virus (TYLCV), and to obtain accessions of determinate tomatoes that are resistant to TYLCV and have high yields.This research method used Completely Randomized Design (CRD) to test the resistance of tomato accessions from TYLCV attack. The second stage of the experiment used a Completely Randomized Block Design (CRBD) to test the yield of tomato accession at the tolerance level forTYLCV resistance. The treatments consisted of 7 F1 tomato hybrids, namely T-26, T-41, T-121, T-122, T-165, T-175, T-187, and 3 control hybrid namely T-90, Liontin and Betavila. The data obtained were analyzed using analysis of variance (ANOVA) then followed by DMRT (Duncan's Multiple Range Test) at a significance level of 5%. The results showed that the control hybrid T-90 was resistant and the T-122 hybrid was moderately resistant to TYLCV (Experiments stages I and II). The seven hybrids tested (T-26, T-41, T-121, T-122, T-165, T-175, and T-187) had the same weight of fruits as the TYLCV resistant control hybrid (T-90). The superior hybrids on the parameters of weight of fruits, weight per fruits, number of fruit, and fruit diameter were T-122 and T-175. Hybrid (F1) which has resistance to TYLCV and high yield is T-122.